Variation in Soil Properties and Topographic Roughness of Stabilized Sand Dunes in the Central Great Plains, USA: Implications for Susceptibility to Reactivation - McKeehan, Kevin G. (My University, 2018)
With a warming global climate, regional climates will undergo changes to their temperature, precipitation, and wind regimes. Consequently, the potential exists for these shifting climatological conditions to affect dunefields across the globe. Sand dunes are found in two states – active and stable, or unvegetated and vegetated, respectively – and the activation of previously stable dunes could have serious ramifications for communities and ecosystems. Yet, the mechanisms of dune reactivation and stabilization are not fully understood. In research presented here, the links between dune and soil variables and dune status are explored within four dunefields in the state of Nebraska on the central North American Great Plains. Specifically, the links between soil particle size, loss-on-ignition (LOI), cation exchange capacity (CEC), soil carbon and nitrogen, and dune surface roughness, which is interpreted as a proxy for relatively recent dune activity, are examined from soil samples taken in the field and GIS analyses. Results show that dunes suspected of a more recent activity because of their rougher surface topography, contain fewer fine particles in surface soils and have low levels of the other soil variables, indicating relatively weak pedogenesis. Likewise, dunes that are surficially smoother and therefore assumed to have been more stable in recent times, have surface soils containing more fine particles, more soil organic carbon, nitrogen, LOI, and a greater CEC. These results suggest pedogenic-geomorphic feedbacks which may incline stable dunes toward increased stabilization and recently active dunes toward future reactivation. For example, frequently reactivated dunes create a choppy, rough landscape which may experience particularly high shear stress during strong winds, making the dunes susceptible to reactivation and less likely to undergo more significant pedogenesis including development of finer texture and accumulation of more soil carbon. This tendency toward stabilization or reactivation has resulted in dunefields with contrasting soil development and surface topography across the study area, despite similar environmental settings.
Includes Figures, Tables, Maps, Imagery, Profiles, Charts, Graphs and Bibliography.
Keywords: Soil properties; Topographic roughness; Central Great Plains; Sand dunes; Dune reactivation; Dune stabilization